Suppressed Band Characteristics of an UWB Conical Monopole Antenna with Split Loops Based on the Equivalent Circuit - Eun-Seok Jang; Che-Young Kim; Dae-Geun Yang; Sung-Su Hong (International Journal of Antennas and Propagation)
In this study, the principle of band suppressing an UWB antenna by attaching a small resonator is explained by developing its equivalent circuit. The realized UWB antenna is a conical monopole antenna that contains a split loop for band suppression. The conical monopole antenna corresponds to a transmission line terminated with load impedance, and the split loop is an LC resonator. The coupling between the conical monopole antenna and the split loop is represented as mutual inductance. Equivalent circuits for the UWB antenna suppressing single band [WLAN] and dual band [WLAN, WiMAX] have been suggested, and these equivalent circuits provide insight into the performance characteristics of the developed band suppressed UWB antenna to which a small sized resonator is installed. Simulation and measurement results on the input impedance and VSWR of the proposed equivalent circuit are closely matched. Thus, the validity of the equivalent circuit is confirmed. The measurement results demonstrate that the proposed antenna exhibits a gain of over 3 dBi in the working band and has an omnidirectional radiation pattern. Band rejection has been also implemented by split loops.